Studi Komparatif Efektivitas Pembelajaran Bahasa Jepang melalui LuvLingua dan YouTube di Era Belajar Mandiri Digital - Kayla Attya Ramadhani; Fikri Saputra; Muhammad Yordi Septian; Fadhlan Zaki Darmansyah; Humannisa Rubina Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The rapid advancement of digital technology has transformed the landscape of language learning, particularly in the post-pandemic era where self-directed learning through mobile applications and online platforms is increasingly common. This study explores the effectiveness of two popular digital tools LuvLingua and YouTube in supporting independent Japanese language learning among Indonesian university students. LuvLingua offers a structured, gamified approach suitable for beginners, while YouTube provides authentic and contextual exposure through real-life content. Using a descriptive quantitative method, this research involved twelve students from non-language majors who actively use both platforms to study Japanese. The findings reveal that each platform has distinct advantages: LuvLingua excels in foundational vocabulary and pronunciation, whereas YouTube significantly enhances listening skills and cultural understanding. The combination of both platforms yields optimal learning outcomes, although success heavily depends on learners’ motivation, discipline, and time management. This study contributes to the growing body of research on technology-assisted language learning and provides practical recommendations for learners, educators, and content developers.